Pengaruh Celebrity Endorser dan Brand Image terhadap Keputusan Pembelian Produk Scarlett whitening : Survei Online pada Konsumen Akun Instagram @Scarlet_whitening - Ai Reka Pebrianti; Ari Arisman; Suci Putri Lestari (CV. Ulil Albab Corp, 2022)
This study aims to determine the effect of simultaneously and partially Celebrity Endorser and Brand Image on Purchase Decisions through a survey on consumers of Scarlet Whitening products. The research method used in this study is a quantitative approach with survey methods. The population in this study is unknown and a sample of 100 respondents was taken. The type of data used in this study is primary data obtained through a questionnaire. Data analysis used was classical assumption test and multiple regression analysis using SPSS version 25. Hypothesis testing used t, F and R² tests. The results showed that Celebrity Endorser and Brand Image simultaneously had a significant effect on purchasing decisions. Celebrity endorsers partially have a significant effect on purchasing decisions and brand image partially has a significant effect on purchasing decisions.